1989
DOI: 10.1093/oxfordjournals.humrep.a136867
|View full text |Cite
|
Sign up to set email alerts
|

Human fertilization by micro-injection of immotile spermatozoa

Abstract: Microfertilization of human oocytes with spermatozoa from a man with immotile cilia syndrome is reported, confirming a preliminary investigation where a zona-free donor oocyte was fertilized with spermatozoa from the same patient. Oocytes from his spouse were obtained by laparoscopy after routine stimulation with clomiphene citrate, human menopausal and chorionic gonadotrophins, and were cultured for 4-6 h in Whittingham's T6 medium, supplemented with 10% of her serum. The spermatozoa were washed and processed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…For a single KS patient SUZI produced a healthy pregnancy whereas ICSI did not [6]. Other successful fertilizations from immotile sperm via sub-zonal insemination have been obtained as well [4,28] without subsequent pregnancies. The Terriou et al report indicated two sets of triplet pregnancies but these were from patients that had 5% non-progressive motility in the semen samples [28].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…For a single KS patient SUZI produced a healthy pregnancy whereas ICSI did not [6]. Other successful fertilizations from immotile sperm via sub-zonal insemination have been obtained as well [4,28] without subsequent pregnancies. The Terriou et al report indicated two sets of triplet pregnancies but these were from patients that had 5% non-progressive motility in the semen samples [28].…”
Section: Discussionmentioning
confidence: 94%
“…Successful treatment of PCD with the birth of healthy babies following embryo transfer on day three or earlier has been reported using sub-zonal insemination (SUZI) [4][5][6] and intracytoplasmic sperm injection (ICSI) [7][8][9][10][11][12][13]. The hypo-osmotic swelling (HOS) test [14] was used in conjunction with ICSI of immotile spermatozoa with success in several cases as well [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In these patients, fertility is impaired through sperm motility. However, since spermatogenesis is not affected, ICSI or in vitro fertilization can still be used to achieve a pregnancy (Bongso et al, 1989), with unknown consequences for the generated offspring.…”
Section: Sex Determination/developmental Abnormalitiesmentioning
confidence: 99%
“…This specific technique of SUZI evolved from animal studies that demonstrated that fertilization and development to birth of healthy live young [3] was possible. Fertilization of human oocytes [24][25][26] and human pregnancies [4] and live births [27] stimulated an increase in the clinical use of this procedure for patients who had failed to achieve fertilization in vitro and for patients with too few (or only immotile) spermatozoa to even attempt in vitro fertilization [28,29]. Pavasuthipaisit et al [30] compared fertilization and embryo development in cattle after SUZI and ICSI, and obtained a higher fertilization with ICSI, although the embryonic development to the hatched blastocyst stage was similar in both groups.…”
Section: Subzonal Sperm Insertion (Suzi)mentioning
confidence: 99%